Analisis Kesalahan Sintaksis dalam Penulisan Artikel Ilmiah Poopuler Siswa Kelas VIII UPTD SMP Negeri 3 Pematangsiantar - Damanik, Chindy; Marlina A. Tambunan; Junifer Siregar; Vita Riahni Saragih; Immanuel Doclas Belmondo Silitonga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of syntactic errors encompassing errors at the phrase, clause, and sentence levels in the writing of popular scientific articles by eighth-grade students of UPTD SMP Negeri 3 Pematangsiantar. This study employed a qualitative descriptive method with data sources in the form of popular scientific article texts written by the students. Data collection techniques were carried out through documentation as well as recording and coding of sentences containing syntactic errors, while data analysis used the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that syntactic errors are still frequently found in students' writing at the phrase, clause, and sentence levels. Errors at the phrase level include inaccurate use of head and modifier elements as well as non-parallelism of coordinative elements; at the clause level, errors include incomplete subject and predicate elements as well as inappropriate use of bound clauses; while at the sentence level, errors include incomplete sentence structures, inappropriate use of conjunctions, ineffective sentences, and ambiguity. These errors are caused by students' lack of understanding of syntactic rules, the influence of regional languages, and insufficient writing practice, so that efforts to improve writing instruction with a greater focus on syntactic structure mastery are needed in order for students to produce writing that is accurate and well-formed.